Evaluation of short-term loop colostomy in dogs using conventional and supporting subcutaneous silicone drain techniques (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed at evaluating the supporting and non-supporting loop colostomy techniques in dogs. Materials and Methods: In this study, 12 adult healthy mongrel dogs were used to carry out a short-term (21 days) temporary flank loop colostomy. The dogs were divided into two groups (n = 6). In the first group (Con group), conventional stoma fixation was operated without loop support. In the second group [subcutaneous silicone drain (SSD) group], an SSD was used as a supporting bridge. The stoma was fixed by a modified, interrupted seromuscular vertical mattress suture pattern. Both peristomal and stomal complications were recorded.  Results: Results showed that a total of seven dogs (58%) suffered complications. There was a significant tendency toward less peristomal (p = 0.012) and stomal complications (p = 0.001) in the SSD group. The intensity of pain was significantly (p < 0.05) different between the two groups in the first week post surgery. Comfort with stoma care was significantly (p = 0.015) better in the SSD group, experiencing the best results.  Conclusion: It is concluded that an appropriate stoma location, using a soft supporting bridge, stoma fixation using modified interrupted neuromuscular vertical mattress sutures, and proper appliance fixation by adhesive tapes and a tight T-shirt may overcome the complications of short-term loop colostomy in dogs and introduce a satisfaction for stoma care.J. Adv. Vet. Anim. Res., 7(4): 685-691, Dec 2020http://doi.org/10.5455/javar.2020.g468